Optimization of Condenser Backwash Method to Maintain Condenser Performance During the Backwash Process in PLTGU Grati - Adin Nurrohman; Purbo Suwandono; M. Agus Sahbana; Gatot Soebiyakto (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2022)
The condenser is a device used to change the water vapor phase that has been used to rotate the turbine blade into a liquid phase by condensing it. When the condenser tube is dirty, it can disrupt the steam condensation process which affects the efficiency of the condenser. To overcome this problem a condenser backwash is carried out. Condenser backwash has a good influence on unit efficiency but backwash activities also reduce production by decreasing vacuum condensers and steam turbine loads. When the vacuum condenser backwash process decreases + - 24 mmHg and the steam turbine load decreases + - 8 MW.The condenser backwash process is carried out from the control room with the observation of parameters from the local area or equipment. Backwash condensers are done one by one as needed. The condenser type in PLTGU Grati Block I is a type of crossflow with two sides, namely, side A and side B. Each side of the condenser has a different sequence backwash condition. This study will be carried out a backwash method that is different from the sequence of automatic sequences.In the normal condenser backwash activity of data table 3 we can know there is a decrease in steam turbine load ± 8MW and a decrease in vacuum ± 24 mmHg. This is because at a certain period the condenser performance is reduced because at the time of switching valve one side of the condenser is not irrigated by seawater so that the heat transfer in the condenser is reduced which has an impact on a load of steam turbine and vacuum condenser. After the research was obtained that the greater the opening of the valve inlet when the condenser backwash then the decrease in vacuum and steam turbine load decreased even no decrease in load.The backwash method that can be done to keep the vacuum condenser and steam turbine load stable is by maneuvering the valve inlet, outlet, and condenser backwash valve. The results of the analysis obtained were a more stable decrease in steam turbine production in 0 MW and a decrease in the vacuum of 14 mmHg.